Forward-Looking MD&A Disclosures and the Information Environment - Muslu, Volkan; Radhakrishnan, Suresh; Subramanyam, K. R.; Lim, Dongkuk (Management Science, 2015)
We use computer-intensive techniques to study the informational properties of forward-looking disclosures in the management discussion and analysis (MD&A) sections of 10-K filings made with the Securities and Exchange Commission. We find that firms make more forward-looking MD&A disclosures when their stock prices have lower informational efficiency, i.e., when their stock prices poorly reflect future earnings information. The greater levels of forward-looking MD&A disclosures help improve yet are unable to completely mitigate the lower informational efficiency of stock prices for such firms. These findings are stronger for operations-related forward-looking disclosures, disclosures that are made prior to 2000, and disclosures made by loss firms. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.1921 . This paper was accepted by Mary Barth, accounting.